Virtual learning environment framework for higher educational institutions in Saudi Arabia - Malkawi, Aminah Rezqallah Hasan (2024)
This research develops and validates a culturally sensitive Virtual Learning Environment (VLE) framework tailored to the specific needs of Higher Education Institutions (HEIs) in Saudi Arabia, leveraging cloud computing to address gaps in existing educational technologies. Aligned with Saudi Arabia's Vision 2030, which emphasizes digital transformation and innovation, this study contributes to the nation's strategic goals of modernizing education and enhancing learning quality. Despite ongoing educational reforms, many VLEs fail to address the unique cultural, educational, legal, and operational needs of Saudi HEIs. The research adopts a mixed-methods approach, beginning with an exploratory phase comprising an extensive literature review and a preliminary study to identify key challenges and requirements of Saudi HEI users. Based on these insights, an initial requirement model for a cloud-based VLE (CBVLE) is developed and refined through three iterative rounds of the Delphi technique, achieving expert consensus exceeding 70%. The finalized requirement model encompasses five core components: cultural considerations and educational, legal, quality, and operational requirements. A significant finding underscores the integration of cultural influences as essential to developing VLEs that meet user needs and ensure sustainable adoption. A partial CBVLE prototype is developed to validate the framework, demonstrating the practical applicability of the requirement model in real-world contexts. This study offers a novel, context-specific contribution to educational technology in Saudi Arabia by presenting a comprehensive VLE framework that leverages cloud computing. By aligning with Vision 2030, the findings provide actionable guidance for HEIs seeking to implement adaptable, user-centred, and technologically advanced VLEs, ultimately supporting national objectives for educational excellence and innovation in Saudi HEIs.